ARDUINO AND IOT-BASED OBSERVATION METHOD FOR MONITORING TEMPERATURE, HUMIDITY, AND AIR PRESSURE OF ELECTRON BEAM ACCELERATOR’S ROOM - Rachmawati, Isti Dian; Linandia, Ismi Putri Mei; Fajarudin, Rizky; Saefurrochman, Saefurrochman; Adabiah, Suhadah Rabi'atul (GANENDRA Majalah IPTEK Nuklir, 2023)
The monitoring system for temperature, humidity and air pressure in the electron accelerator’s room has been designed. This research is based on operational environmental monitoring procedures in the accelerator room that must be carried out before the accelerator operates. We offer a simple and adaptable monitoring solution for the electron accelerator room. Parameter data can be monitored using a smart device. Operators do not need to go into the accelerator room to carry out environmental monitoring. The proposed system uses Arduino technology and the Internet of Things (IoT). Data acquisition programming was performed using Arduino IDE and ESP8266 NodeMCU as microcontrollers. The microcontroller then transmits temperature, humidity, and pressure data parameters to the cloud server, where they are then displayed on the smart device via the Blynk app. The results show that the system that has been designed is able to read and store parameter readings on the sensors used and the system has been able to make decisions in the form of notifications about whether the Electron Beam Machine is ready or not to be operated.